Molecular farming in plants: Recent advances and future prospects - Ma, Shengwu; Wang, Aiming (Springer Netherlands, 2012)
Since the first recombinant plant-derived pharmaceutical protein (PDP), i.e., human serum albumin, was produced in transgenic tobacco and potato plants in 1990, molecular farming in plants has emerged as a new subject of sciences. The plant system has the potential to provide virtually unlimited quantities of these bio-products at low costs, which is impossible for any other systems. plants have been vigorously tested for the production of numerous bio-products including vaccines, therapeutic proteins, industrial enzymes and proteins with other functions. The urgent demand from the rapidly growing market has also facilitated research & development in the downstream processing of plant-derived recombinant proteins. Various breakthroughs resulting from basic to practical research  have lead to the rapid advance of this subject. This book was written by international authorities and was anticipated to help biotechnologists, scholars, professors, teachers and students in the field with a comprehensive state-of-the-art of overview of the subject. The book consists of 12 chapters, elucidating the principles of molecular farming, summarizing the most recent advances, revealing current challenges and pointing out future research directions.